3d Printing: 3D‐Printing of Functional Biomedical Microdevices via Light‐ and Extrusion‐Based Approaches (Small Methods 2/2018). Issue 2 (9th February 2018) - Hwang, Henry H.; Zhu, Wei; Victorine, Grace; Lawrence, Natalie; Chen, Shaochen
Abstract : In article number1700277, Shaochen Chen and co‐workers review 3D‐printing technologies, in the context of creating functional biomedical microdevices, considering techniques such as extrusion‐based and light‐based 3D printing and discussing the advantages and limitations, with respect to other classes of 3D printing. In particular, the fabrication of micromachines/robotics, drug‐delivery devices, biosensors, and microfluidics is addressed.